Strengthening memory: The impact of resistance training on cognitive health in aging and cognitive impairment - Ennahli, Khaoula; Miguel, Diogo (Journal of Sports Research, 2026)
This review examines resistance training (RT) as a pathway for preserving declarative memory in later life, addressing a critical gap in the literature where RT has been largely subsumed under general physical activity despite its distinct neurobiological profile. We aimed to clarify whether RT uniquely supports declarative memory vulnerable to healthy aging, mild cognitive impairment, and early neurodegenerative pathology. We conducted a multilevel synthesis of evidence from randomized controlled trials, neuroimaging studies, electrophysiology, and molecular research examining RT effects on memory, brain structure, network connectivity, and underlying biological mechanisms. Particular attention was given to hippocampal subfields, default-mode and fronto-hippocampal networks, and exercise-responsive neurotrophic, vascular, metabolic, and inflammatory pathways. Across modalities, converging evidence indicates that RT attenuates hippocampal and precuneus atrophy, preserves white-matter integrity, strengthens functional connectivity within memory networks, and enhances neural efficiency indexed by oscillatory and event-related electrophysiological markers. Biologically, RT reliably increases insulin-like growth factor-1 and improves insulin sensitivity, endothelial function, and inflammatory balance, creating a plastic milieu that supports hippocampal resilience. Cognitive benefits are most consistent in mild cognitive impairment, with parallel improvements in mood, functional independence, and quality of life. These findings position RT as a scalable, cost-effective intervention that compares favorably with other intervention modalities. Progressive RT should be considered a core component of prevention and care strategies for cognitive aging, with implications for clinical practice, community programs, and public health policy.